Caracterização estrutural das substâncias húmicas aquáticas extraídas dos rios itapanhaú e ribeira de iguape - Goveia, Danielle [UNESP]; Rocha, Julio Cesar [UNESP]; De Oliveira, Luciana Camargo; De Morais, Leandro Cardoso [UNESP]; De Campos, Valquiria [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Rosa, André Henrique [UNESP] (My University, 2011)
The knowledge of the structure characteristic of the Organic Matter is important for the understanding of the natural process. In this context aquatic humic substances (principal fraction) were isolated from water sample collected from the two distinct rivers, using procedure recommended for International Humic Substances Society and characterized by elemental analysis, electron paramagnetic resonance and nuclear magnetic resonance (13C NMR). The results were interpreted using principal component analysis (PCA) and the statistical analyses showed different in the structural characteristics of the aquatic humic substances studied.
Structural caracterization of aquatic humic substance extracted from itapanhaú and ribeira de iguape rivers
Keywords: Aquatic humic substances; Principal component analysis; Structural characterization